Gross anatomy workbook - Gandotra, Achleshwar (Jaypee, 2019)
The Gross Anatomy Workbook was initially created to facilitate the learning of Anatomy. It has been 18 long years when the first edition of the book was published. Since then, medical education has undergone a sea change. The concept of teaching-learning process has also been revamped. Keeping these things in mind, it became necessary to upgrade the workbook and make it student savvy. Therefore, relevant text has been added to the illustrations so that the students can revise gross anatomy and prepare themselves for the viva voce. Moreover, many redundant diagrams have been deleted and no text has been provided with some illustrations as they are self-explanatory. Students will definitely be benefitted by this effort.